Urea removal strategies for dialysate regeneration in a wearable artificial kidney. (March 2020) - van Gelder, Maaike K.; Jong, Jacobus A.W.; Folkertsma, Laura; Guo, Yong; Blüchel, Christian; Verhaar, Marianne C.; Odijk, Mathieu; Van Nostrum, Cornelus F.; Hennink, Wim E.; Gerritsen, Karin G.F.
Abstract: The availability of a wearable artificial kidney (WAK) that provides dialysis outside the hospital would be an important advancement for dialysis patients. The concept of a WAK is based on regeneration of a small volume of dialysate in a closed-loop. Removal of urea, the primary waste product of nitrogen metabolism, is the major challenge for the realization of a WAK since it is a molecule with low reactivity that is difficult to adsorb while it is the waste solute with the highest daily molar production. Currently, no efficient urea removal technology is available that allows for miniaturization of the WAK to a size and weight that is acceptable for patients to carry. Several urea removal strategies have been explored, including enzymatic hydrolysis by urease, electro-oxidation and sorbent systems. However, thus far, these methods have toxic side effects, limited removal capacity or slow removal kinetics. This review discusses different urea removal strategies for application in a wearable dialysis device, from both a chemical and a medical perspective.